Dialogues of digital commons and equitable resilience - Toursoglou-Papalexandridou, Danai (Sens public)

(untitled) (Département des littératures de langue française, 2024)
During the first wave of 2020 pandemic, a rise in numbers and popularity of commons-based initiatives was observed worldwide, either in digital or cyber-physical form. From the open-source distribution and production of healthcare equipment to the installation of community fridges, such initiatives have influenced the resilience potential of communities. This research analyses disasters as an outcome of vulnerability and risk and seeks links between resilience and commons-based initiatives. It places the emergent digital and cyber-physical commons-based initiatives within metropolitan ecosystems and proposes the measurement of their reflections on the resilience of greater areas. That way, an equitable perspective on resilience measurements is proposed through the analysis of bottom-up initiatives and the inclusion of underrepresented groups. The paper consists of a literature review in the fields of resilience, social capital, commons-based initiatives and ecosystems, providing examples from Boston (MA, USA), Medellín (Colombia) and Athens (Greece). This research, being published after the first shock and within the constant stretch of the 2020 pandemic, aims at opening a discussion and adding to the academic knowledge a more equitable resilience perspective, as well as supporting and framing the impact of commons-based initiatives.